2011
DOI: 10.4049/jimmunol.1003173
|View full text |Cite
|
Sign up to set email alerts
|

Two-Step Binding of Transcription Factors Causes Sequential Chromatin Structural Changes at the Activated IL-2 Promoter

Abstract: Most gene promoters have multiple binding sequences for many transcription factors, but the contribution of each of these factors to chromatin remodeling is still unclear. Although we previously found a dynamic change in the arrangement of nucleosome arrays at the Il2 promoter during T cell activation, its timing preceded that of a decrease in nucleosome occupancy at the promoter. Here we show that the initial nucleosome rearrangement was temporally correlated with the binding of NFAT1 and AP-1 (Fos/Jun), whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…A recent paper suggested a two-step process in the assembly of a transcription factor complex on the IL-2 promoter. NFAT1, Jun, and Fos are the early and Oct2, Rel A (p65), c-Rel, and NFAT2 are the late binding factors, respectively (75). Thus, sequential binding of transcription factors and coactivators are probably essential and general series of events for the TCR-induced IL-9 expression also.…”
Section: Discussionmentioning
confidence: 99%
“…A recent paper suggested a two-step process in the assembly of a transcription factor complex on the IL-2 promoter. NFAT1, Jun, and Fos are the early and Oct2, Rel A (p65), c-Rel, and NFAT2 are the late binding factors, respectively (75). Thus, sequential binding of transcription factors and coactivators are probably essential and general series of events for the TCR-induced IL-9 expression also.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation through the TCR and CD28 is accompanied by posttranslational modification of histones and remodeling of a positioned nucleosome within the Il2 upstream regulatory region (10,20,29,30,33,34). This can be observed in recent DNase I hypersensitivity mapping data sets from the ENCODE project (18).…”
Section: Gray Asterisk) Costimulation Of Naive Cd4mentioning
confidence: 82%
“…After several hours of stimulation lower levels of IL-2 transcriptional activity are observed (Ishihara and Schwartz, 2011; Nguyen et al, 2010). Coincident with this, NFATc1 can be detected at the IL-2 promoter (Ishihara and Schwartz, 2011; Nguyen et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…After several hours of stimulation lower levels of IL-2 transcriptional activity are observed (Ishihara and Schwartz, 2011; Nguyen et al, 2010). Coincident with this, NFATc1 can be detected at the IL-2 promoter (Ishihara and Schwartz, 2011; Nguyen et al, 2010). We have previously shown that NFATc1 is not capable of synergistically activating IL-2 transcription with cJun nor interacting with cJun homodimers off of DNA, which is consistent with the fact that NFATc1 lacks a C-terminal activation domain (Nguyen et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation